Human Capital Project : Year 3 Progress Report - Human Capital Project (World Bank, Washington, DC, 2022)
Year 3 of the Human Capital Project (HCP) has been one in which countries have struggled to stem their losses. COVID-19 (coronavirus) has both disrupted and caused devastating setbacks to lives and livelihoods. Globally, we have lost an estimated decade worth of gains in human capital outcomes. With over 255 million jobs equivalent erased and 1.6 billion children out of school at the peak of school closures, poverty is set to significantly increase for the first time in 20 years, particularly in low-income countries and Sub-Saharan Africa. The poor and vulnerable have also endured the hardship of natural disasters and conflict. In the face of these challenges, we are more committed than ever to help countries invest optimally in their people, prevent hard-won human capital gains from being eroded further, and build back better to ensure green, resilient and inclusive development. Human capital has been adopted as a special theme for the 20th replenishment of the World Bank’s International Development Association (IDA-20). The HCP network has grown to 82 countries and, even in this unique year of travel bans and social distancing, we have maintained a high level of engagement through online ministerial conclaves and global forums, multilingual knowledge exchange webinars including on COVID-19 strategies, knowledge products, and country-specific case studies of successful human capital interventions.